Surgical Repair of Two Kinds of Type A Aortic Dissection After Thoracic Endovascular Aortic Repair - Fang, Zhou; Li, Haiyang; Warburton, Thomas M.; Zhu, Junming; Liu, Yongmin; Sun, Lizhong; Jiang, Wenjian; Zhang, Hongjia (Frontiers in Cardiovascular Medicine, 2022)
Background: Retrograde dissection is now recognized as an important complication following thoracic endovascular aortic repair (TEVAR). The purpose of this study is to describe two different situations of TAAD after TEVAR. We will introduce the surgical methods used to repair TAAD following TEVAR at our center, and evaluate its long-term prognosis. Methods: Between January 2010 to October 2019, 50 patients who had previously received TEVAR treatment for TBAD were admitted to our center for repair of a type A aortic dissection. According to the patients’ CT angiographies and intra-operative findings, we identified two distinct groups: a retrograde group (stent-induced new aortic injury, with retrograde extension involving the ascending aorta) and an antegrade group (entry tear located in the aortic root, ascending aorta or the aortic arch, away from the edges of the stent grafts). The options for treatment of the proximal aorta were Bentall procedure (12/50, 24.0%) and ascending aorta replacement (38/50, 76.0%). All patients underwent total arch replacement (TAR) and frozen elephant trunk (FET) implantation. Survival over the follow-up period was evaluated with the Kaplan-Meier survival curve and the log-rank test. Results: The median interval time from prior TEVAR to reoperation was 187 days (IQR:30.0, 1375.0 days). 18.0% of TAAD after TEVAR did not have any obvious symptoms at the time of diagnosis, most of which were found on routine follow-up imaging. The patients in the retrograde group were younger than those in the antegrade group (44.0 ± 9.4 vs. 51.4 ± 10.5 years, P=0.012). No significant differences in the incidence of postoperative complications or mortality were noted between the two groups. The mean follow-up time was 3 years. No late death or complications occurred after one year following surgery upon follow-up. The asymptomatic survival rate one year after surgery was 90.0%. Conclusions: The TAR and FET technique was feasible and effective for complicated TAAD after TEVAR. The surgical success rate and long-term prognosis of patients undergoing the timely operation are satisfactory.